Energy systems engineering evaluation and implementation - Vanek, Francis M.; Albright, Louis; Angenent, Largus (New York, NY McGraw-Hill Education, 2016)
Fully updated to cover the latest energy systems and technologies, this edition offers a balanced analytical approach to assessing options and making decisions about energy systems, while emphasizing a portfolio approach in which a range of energy options are employed rather than one technology.
Keywords: Power (Mechanics); Energy conservation; Electronic books